Implementation of Environmental Management Accounting (EMA) in Supporting Sustainable Business Strategy - Munir, Alchudri (Pt. Anagata Sembagi Education, 2026)
Sustainability has become an essential component of modern business strategy as organizations face increasing environmental challenges, regulatory pressures, and stakeholder expectations. Companies are required to integrate environmental considerations into strategic decision making to achieve long term competitiveness and responsible resource management. Environmental Management Accounting (EMA) has emerged as an important managerial tool that provides information on environmental costs, resource use, and environmental performance to support sustainability oriented strategies. This study aims to analyze the role of Environmental Management Accounting in supporting sustainable business strategy within organizations. The research employed a quantitative approach using a survey method involving managers, accountants, and sustainability officers in organizations implementing environmental management practices. Data were collected through structured questionnaires and analyzed using descriptive statistics and multiple regression analysis to examine the influence of EMA implementation on sustainable business strategy. The results indicate that the implementation of EMA significantly contributes to sustainability oriented strategic decision making, particularly through environmental cost identification, resource efficiency management, and integration of environmental information in managerial processes. EMA practices enable organizations to improve environmental performance while enhancing operational efficiency and long term competitiveness. The study concludes that Environmental Management Accounting plays a strategic role in bridging environmental sustainability and financial management, thereby supporting the development of sustainable business strategies and organizational resilience in the evolving business environment.